PERANCANGAN UI/UX APLIKASI RESERVASI PANGKAS RAMBUT DENGAN METODE DESIGN THINKING - Syilla Arviani Putri Aisyah; Muhammad Labib Jundillah; Muhammad Rivani Ibrahim (Institut Teknologi dan Bisnis (ITB) Swadharma, 2026)
This study aims to design UI/UX recommendations for a Barbershop reservation application using the design thinking method and assess its usability using the System Usability Scale (SUS). The research method includes five stages of Design thinking: empathize, define, ideate, prototype, and test. Data were collected through customer observation and interviews, as well as literature studies related to UI/UX. Prototype testing was conducted using Maze and the SUS questionnaire via Google Form to evaluate the design's effectiveness and efficiency. The study produced a complete design consisting of a task flow, sitemap, low-fidelity wireframe, high-fidelity prototype, and an admin dasboard that includes reservation management features and real-time barber status settings. The research focuses on adapting design thinking to the operational context of Sky Barbershop, adding a